2010
DOI: 10.1159/000320234
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous <i>Malassezia</i> Microbiota in Atopic Dermatitis Patients Differ by Gender and Body Part

Abstract: Background:Malassezia is a particularly important factor in the occurrence of atopic dermatitis (AD).Aim: The aim of this study was to quantitatively clarify the Malassezia species isolated from AD patients by gender, body part and analytical method in detail. Methods: The subjects were 20 AD males and 47 AD females. Samples were collected from lesion and nonlesion areas on the face and upper trunk of AD patients. Malassezia DNA was analyzed using a real-time PCR system. Results: The cutaneous Malassezia micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…However, conventional culture and identification methods offer the advantage of further evaluating the isolates for possible virulence factors, such as the production of phospholipase (44,170) and indole (108,184,336) and melanin synthesis (107). Furthermore, this was highlighted in a study by Akaza et al (6), in which the seasonal rates of isolation of Malassezia species from healthy skin determined by quantitative PCR (qPCR) were compared with those determined by use of Leeming-Notman agar (197). Increased Malassezia colonization of the skin in summer was determined by culture but not by PCR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, conventional culture and identification methods offer the advantage of further evaluating the isolates for possible virulence factors, such as the production of phospholipase (44,170) and indole (108,184,336) and melanin synthesis (107). Furthermore, this was highlighted in a study by Akaza et al (6), in which the seasonal rates of isolation of Malassezia species from healthy skin determined by quantitative PCR (qPCR) were compared with those determined by use of Leeming-Notman agar (197). Increased Malassezia colonization of the skin in summer was determined by culture but not by PCR.…”
Section: Resultsmentioning
confidence: 99%
“…Such cycles of population growth, bioactive indole production, and subsequent deprivation of nutrients could result in insufficiently masked antigens and ligands on the surface of the yeast cells, which would result in the activation of the immune system. One study showed that increased numbers of metabolically active cells during summer resulted in higher rates of isolation in culture medium than in fall, although the actual DNA loads were equal in both seasons (6). The difference in the rates of active versus stationary/dead yeasts cells would result in the differential regulation of the skin immune response (316).…”
Section: Seborrheic Dermatitismentioning
confidence: 99%
“…The skin microbiome in patients with AD was assessed in 11 studies, Table 1 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66. A greater proportion of longitudinal studies and 2 completed randomized controlled trials were performed in AD patients.…”
Section: Resultsmentioning
confidence: 99%
“…The procedure used for the analysis of skin-resident microorganisms was based on our previous report [10]. For the analysis of Propionibacterium spp., 0.05 ml of collected samples and buffer-diluted samples were cultivated on modified GAM agar medium (Nissui Pharmaceutical, Tokyo, Japan) at 35°C for 7 days under anaerobic conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Malassezia spp. were analyzed by real-time PCR using 3 ml of the collected samples in accordance with our previous studies [10,11]. …”
Section: Methodsmentioning
confidence: 99%